Benelux and European Union CFSP Security in Response to the Russia-Ukraine War - Kurniasih, Dedeh; Nugrahani, Henny Saptatia Drajati (Journal of Strategic and Global Studies, 2023)
This study discusses the security cooperation of the three countries of Belgium, the Netherlands, and Luxembourg. In particular, this paper elaborates on its role in the Common Foreign and Security Policy (CFSP) adopted by the European Union in responding to the Russia-Ukraine Conflict, 2014-2022. The method used in this research is qualitative with analytical descriptive. The research source uses secondary data in the form of literature review. This study is analyzed using the theory of Regional Security Complex (RSC) and the Concept of Cooperative Security. RSC theory is used to analyze the cooperation of Benelux as a regional power in developing European Union CFSP security cooperation. Result shows that Benelux is not brave enough to make a decision which is completely different from the EU public. The Benelux countries’ position is to agree with the EU's decision on the Russia-Ukraine war.